2013
DOI: 10.1103/physrevd.88.123004
|View full text |Cite
|
Sign up to set email alerts
|

Interacting viscous dark fluids

Abstract: We revise the conditions for the physical viability of a cosmological model in which dark matter has bulk viscosity and also interacts with dark energy. We have also included radiation and baryonic matter components; all matter components are represented by perfect fluids, except the dark matter, that is treated as an imperfect fluid. We impose upon the model the condition of a complete cosmological dynamics that results in an either null or negative bulk viscosity, but the latter also disagrees with the Local… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 66 publications
2
74
0
Order By: Relevance
“…This kind of interaction mechanism has shown to be compatible with the current data [31]. In the context of viscous fluids, the interaction between dark matter and dark energy was studied in [21]. It has been shown that, under the ansatz ζ j = ζ j (H ), low-redshift data favors a positive definite value of the bulk viscosity, whereas high-redshift data prefers a negative value of the bulk viscosity.…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…This kind of interaction mechanism has shown to be compatible with the current data [31]. In the context of viscous fluids, the interaction between dark matter and dark energy was studied in [21]. It has been shown that, under the ansatz ζ j = ζ j (H ), low-redshift data favors a positive definite value of the bulk viscosity, whereas high-redshift data prefers a negative value of the bulk viscosity.…”
Section: Introductionsupporting
confidence: 60%
“…This ansatz avoids the degeneracy problem associated with the case when the bulk viscosity is taken as ζ j = ζ j (H ) [20]. However, in [22], the same scenario was studied, from the dynamical system point of view, finding that viscous phantom solutions with stable behavior are not allowed in the framework of complete cosmological dynamics [21,30]. In the present paper we work along these lines by including an interaction between the dark matter and the dark energy.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations